Advances in management accounting. Vol. 25 - Epstein, Marc J.; Lee, John Y. (Advances in management accounting,, 2015)
Advances in management accounting publishes thoughtful, well-developed articles across a broad spectrum of current topics in the field of management accounting, using a variety of research methods including survey research, field tests, corporate case studies and modeling. Volume 25 exemplifies the broad scope of Advances in management accounting, examining a number of key areas in management accounting.